Paediatric society: ongoing initiatives to raise the profile of paediatrics. (24th May 2012) - Zhu, H; Balendran, G; Xiang, N; Badcock, A; Xie, F; Bhanu, C; Diviney, J; Creamer, A; Parker, A; Kelsall, W
Abstract : Aims: To assess baseline paediatric career intentions and the impact of a student-led paediatric society (PS), which aims to increase student exposure and encourage recruitment to paediatrics. The PS was established in 2009 and runs career events, paediatric/neonatal resuscitation training days, Teddy Bear Hospital (TBH) sessions and provides information for electives. Methods: Clinical students (2011) joining the PS completed a baseline career choice questionnaire during their introductory week. After attending PS events, students completed anonymous feedback questionnaires to assess changes in attitudes towards paediatrics. Participation in TBH, paediatric electives and student selected components (SSC) were used as other indicators of interest in paediatrics. Results: The PS has 288 members, representing 64% of clinical students. 53 students responded to the baseline careers questionnaire; of these, 7 (13%) planned to specialise in paediatrics and mean certainty about their future career choice was 2.5 (5-point Likert scale). 30 students attended our careers event in November 2011 and 16 completed the feedback questionnaire; 8 were certain they wished to specialise in paediatrics and a further 8 considering paediatrics. The mean value for certainty about their future career was 3.2 (5-point Likert scale). Students (n=30) attending our Paediatric / Neonatal resuscitation training day rated it a mean of 100% for satisfaction and 97% for increased confidence in dealing with future emergency scenarios. The PS organised 8 TBH health education events for local primary schools, involving over 100 medical student volunteers and 250 children. Over the last 4 years the number of students undertaking paediatric electives has increased from 26 to 42 and SSCs from less than 10 in 2007 to 34 in 2011. Conclusions: ▶ The majority of students entering clinical medicine are unsure about their future career choice, but many consider paediatrics as an option. ▶ Events run by the PS with supportive consultants are popular. ▶ Increasing student involvement in TBH, paediatric electives and SSCs has increased the profile of paediatrics at this medical school.